552 The impact of family-work imbalance on self-perceived health: modifying effect of social support. (24th April 2018) - Tasyikan, Hale Arik; Demiral, Yucel
Abstract : Introduction: Work and family imbalance is an important determinant of worker's health. The research on the effects of multiple roles on health in developing countries is scarce. The aim of this study was to investigate the effect of work-family imbalance on self-perceived health (SPH) and to assess the modifying effect of job insecurity (JI), social support at home (SSH), and at work (SSW). Methods: This is a population-based cross-sectional study. The study sample was randomly derived from employed individuals aged 30–64 who participated in 'Balcova Heart Project'. 191 men and 216 women were included in the analyses. Dependent variable was SPH and main independent variables were work-family conflict (WFC), and family-work conflict (FWC). JI, SSH and SSW were considered as possible effect modifiers. Mainly logistic regression models were used. Results: Mean age was 41.9±6.3 and 39.4±6.3 for men and women. Women were more likely to work in white-collar jobs, more educated and have better economic status perception than men. FWC and WFC were independently associated with increased odds of poor SPH [age adjusted odds ratios (OR)=2.92 (1.47–5.78), and 2.38 (95% CI: 1.22 to 4.67) respectively] for women, but there was no significant association for men. In advanced analyses, both SSW and SSH were found to be effect modifiers of the association between FWC and SPH in women (p<0.001). However, the significant association of WFC with SPH disappeared after the adjustment with SSW, therefore, SSW considered to be a confounder for the associations of WFC. Only the association between JI and SPH was significant [odds ratio (OR)=2.52 (1.22–5.21)] in men. Discussion: Both FWC and WFC are important determinants of worker's psychosocial health. Further studies should explore effective population prevention strategies to diminish FWC and WFC, especially in women in developing countries.